Competing organisational perspectives on rapid urbanisation and its management: a case study of Ulaanbaatar, Mongolia. Issue 2 (April 2017) - Anderson, Raven; Hooper, Michael
Abstract : This article draws on the experience of Ulaanbaatar, Mongolia, to understand better the competing perspectives of international and domestic organisations with regard to rapid urbanisation and its management. Over the past two decades, diverse organisations have converged on Ulaanbaatar to address the environmental, spatial and social challenges produced by rapid growth. Interviews with representatives of 18 international and domestic organisations reveal that, while there is agreement concerning the city's main challenges, there is also a lack of consensus about how best to tackle them. This has led to a proliferation of plans, in which local organisations' perspectives are often given relatively little attention. Nonetheless, local government acts on particularly Mongolian perspectives on land use and housing, leading to a divergence between plans and action. We argue that the divide between international and local organisational actors is likely to further reduce the city's ability to effectively cope with rapid urban growth.